Peanut ball for decreasing length of labor: A systematic review and meta-analysis of randomized controlled trials. (November 2019) - Grenvik, Jessica M.; Rosenthal, Emily; Saccone, Gabriele; Della Corte, Luigi; Quist-Nelson, Johanna; Gerkin, Richard D.; Gimovsky, Alexis C.; Kwan, Mei; Mercier, Rebecca; Berghella, Vincenzo
Abstract: Introduction: Prolonged length of labor is associated with increased maternal and neonatal complications. Therefore, great attention has been given to interventions aimed at reducing the length of labor. One such intervention is the peanut ball, a large elongated exercise ball placed between a woman's legs during labor. Objective: The aim of this systematic review and meta-analysis of randomized controlled trials (RCTs) was to assess the effect of the use of peanut ball in reducing length of labor. Study Design: Data sources: MEDLINE, EMBASE, Web of Sciences, Scopus, ClinicalTrial.gov, OVID and Cochrane Library were searched from inception until January 2019. Selection criteria: Selection criteria included RCTs of laboring women with singleton gestations in cephalic presentation at term (≥37weeks) who were randomized to either use of peanut ball or control group (no peanut ball). Data Collection and Analysis: Four trials with 648 nulliparous and multiparous women in spontaneous or induced labor were identified and included. 330 women were randomized to the intervention (peanut ball between the knees during labor) and 318 women to the control. Summary measures were reported as mean difference (MD) with 95% of confidence interval (CI) using the random effects model of DerSimonian and Laird. The primary outcome was total length of labor. PROSPERO Registration Number: CRD42018082438 Results: Total length of labor was 79 min shorter in the peanut ball group, but this was not significant (MD −79.1 min, 95% CI −204.9, 46.7). Peanut ball use showed trends toward higher incidence of spontaneous vaginal deliveries (RR 1.1, 95% CI 1.0, 1.2) and lower incidence of cesarean deliveries (RR 0.8, 95% CI 0.6, 1.0). Conclusions: Peanut ball use was not associated with a significant decrease in total length of labor. Since there were trends toward reductions in length of labor, an increased incidence in spontaneous vaginal deliveries, and lower incidence of cesarean deliveries, more research is needed.